Caspofungin for treatment of invasive aspergillosis in Germany: results of a pre-planned subanalysis of an international registry - Egerer, Gerlinde (European journal of medical research, 2012)
This study is a pre-planned country-specific subanalysis of results in Germany from a multinational multicenter registry to prospectively assess real-world experience with caspofungin administered for treatment of proven or probable invasive aspergillosis (IA).
Gesehen am 18.06.2019